Description of a new species of Parancistrus (Siluriformes: Loricariidae) from the rio Xingu, Brazil - Lúcia H. Rapp Py-Daniel; Jansen Zuanon (Neotropical Ichthyology)
Parancistrus nudiventris, new species, is described and compared with the congener P. aurantiacus. The new species has only been recorded from rio Xingu and can be distinguished from P. aurantiacus by having a naked abdomen (plated in P. aurantiacus), the presence of bluish dots in living specimens or spotted in preserved specimens (uniformly dark or clear brown or mottled, never spotted in P. aurantiacus), larger interbranchial distance (39-56% in HL vs. 24.9-39.5% in P. aurantiacus), narrower interorbital distance (26.8-38% in HL vs. 38.5-43.1% in P. aurantiacus). Parancistrus nudiventris also has buccal teeth more conspicuous than in P. aurantiacus. Main skeletal differences include the presence of a strong condyle on the lateral ethmoid for articulation with the metapterygoid in P. nudiventris (not seen in P. aurantiacus); anguloarticular processes short in P. nudiventris (long in P. aurantiacus); opercle with odontodes, partly exposed in P. nudiventris (completely embedded in skin in P. aurantiacus).